The Effect of Organic Fertilisers on Arbuscular Mycorrhizal Fungi Diversity in the Rizhosphere of Coffea arabica Plants on the Napu Highland, Central Sulawesi, Indonesia - Annadira; Yusran; Wardah; Imran Rachman; Abdul Hadid (Postgraduate, University of Mataram, 2025)
Coffea arabica plantations in Central Sulawesi are carried out on the Napu highland, where this area is dominated by ultisol or yellow red podzolic soils, which have problems of high soil acidity and low availability of macro nutrients. This study used a completely randomised design method consisting of four treatments namely; without organic fertilisers (control)/P0, Leucaena leucocephala leaf compost 3 Kg/tree (P1), Samanea saman leaf compost 3 Kg/tree (P2), Tithonia diversifolia leaf compost 3 Kg/tree (P3), Cow and goat manuire 3kg/tree (P4). The results showed that there were 10 species of Arbuscular Mycorrhizal Fungi (AMF) associated with Coffea arabica plants namely Glomus sp1, Glomus sp2, Glomus sp3, Glomus sp4, Acaulospora sp1, Acaulospora sp2, Acaulospora sp3, Gigaspora sp1, Gigaspora sp2 and Gigaspora sp3. Furthermore, the higher density of FMA spores was found in the treatment without organic fertiliser application/control (P0) which was 31 spores/10 g soil, compared to the treatment of Tithonia diversifolia leaf compost treatment (P3) with 11 spores/10 g soil, cow and goat manure treatment (P4) with 3 spores/10 g soil, and Samanea saman leaf compost treatment (P2) with 2 spores/10 g soil. And in the Leucaena leucocephala leaf compost treatment (P1), no AMF spores were found. The difference in AMF spore density in the various organic fertiliser treatments mentioned above is related to the effect of improving soil chemical properties on the soil. The results of this study contribute to the understanding of the importance of soil amendments with organic fertilisers for the improvement of organic and sustainable arabica coffee production in the future.